Grassroots Asian theology : thinking the faith from the ground up - Chan, Simon (Downers Grove, IL : InterVarsity Press, 2014)
"Much of what the West knows as Asian theology consists largely of elitist accounts of what Asian theologians are saying, and elitist theologians seldom take grassroots Christianity seriously. Yet it is at the grassroots level that we encounter a vibrant, albeit implicit, theology. It is this theology that I wish to highlight."--pref
Contents: Methodological questions--God in Asian contexts--Humanity and sin--Christ and salvation--The Holy Spirit and Spirituality-- The Church.
Includes bibliographical references and index
Keywords: Theology. Doctrinal -- Asia